2015
DOI: 10.1121/1.4923364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient hydrostatic pressure on the material properties of the encapsulation of an ultrasound contrast microbubble

Abstract: Ultrasound contrast microbubbles experience widely varying ambient blood pressure in different organs, which can also change due to diseases. Pressure change can alter the material properties of the encapsulation of these microbubbles. Here the characteristic rheological parameters of contrast agent Definity are determined by varying the ambient pressure (in a physiologically relevant range 0-200 mm Hg). Four different interfacial rheological models are used to characterize the microbubbles. Effects of gas dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Attenuation measured at 0 mm Hg after temporarily subjecting the suspension to 200 mm Hg for 3 minutes showed result similar to that obtained without any pressure change indicating little irreversible destruction of microbubbles under pressure change (Kumar and Sarkar 2015). An identical conclusion was drawn by Hoff through similar attenuation measurement (Hoff 2001)).…”
Section: The Size Distribution and Changes With Ambient Pressuresupporting
confidence: 73%
See 2 more Smart Citations
“…Attenuation measured at 0 mm Hg after temporarily subjecting the suspension to 200 mm Hg for 3 minutes showed result similar to that obtained without any pressure change indicating little irreversible destruction of microbubbles under pressure change (Kumar and Sarkar 2015). An identical conclusion was drawn by Hoff through similar attenuation measurement (Hoff 2001)).…”
Section: The Size Distribution and Changes With Ambient Pressuresupporting
confidence: 73%
“…In our earlier publications (Chatterjee and Sarkar 2003, Kumar and Sarkar 2015, Paul, Katiyar 2010, Paul, Russakow 2013 we have described the procedure in detail for determining the encapsulation properties of an encapsulation based on different models using attenuation data. Here, attenuation is measured in an air-tight set-up that can control the ambient pressure with an accuracy of 0.07 kPa (Figure 1a and b) using an unfocused broadband transducer (Olympus NDT, Waltham, MA, USA) with a central frequency of 3.5 MHz (-6dB bandwidth 2.5 to 4.99 MHz).…”
Section: B Estimating the Encapsulation Parameters Using Attenuationmentioning
confidence: 99%
See 1 more Smart Citation
“…The safe and effective application of UCAs in ultrasound imaging and therapy requires accurate characterization of the physical and acoustic behavior of UCAs (Mulvana et al 2016). Previous studies have demonstrated that the acoustic response and stability of UCAs are influenced by the acoustic pressure (Shi et al 1999; Yeh and Su 2008), fluid-viscosity (Helfield et al 2016), ambient pressure (Forsberg et al 2005; Kumar and Sarkar 2015), gas exchange (Kabalnov et al 1998; Kanbar et al 2017; Shekhar et al 2014), size distribution (Gorce et al 2000; Shekhar et al 2013), temperature (Guiot et al 2006; Mulvana et al 2010), and shell properties (Borden et al 2005; van Rooij et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although many models of microbubble oscillation have been reported (Faez et al 2013), the model from de Jong et al (de Jong and Hoff 1993) was chosen. When linear approximations are employed at low acoustic pressures, the results of these models are equivalent (Kumar and Sarkar 2015). …”
Section: Discussionmentioning
confidence: 99%